Pengaruh Karakteristik Komite Audit dan Rasio Keuangan terhadap Pengungkapan Modal Intelektual - Salsabila Tizmi; Elvira Luthan; Annisaa Rahman (Universitas Batanghari Jambi, 2022)
This research is aimed to examine the influence of characteristic of audit committee and financial ratio to intellectual capital disclosure. Characteristic of audit committee was identified by size of audit committee and meeting of audit committee. Intellectual capital disclosure was proxied by disclosure index, while financial ratio was measured by Return On Assets (ROA) and Debt to Equity Ratio (DER). The study used 17 companies as a sample from a population of 20 BUMN go public companies listed on Indonesian Stock Exchange in the period of 2012-2017. The sample was determined by using purposive sampling. The results showed that characteristic of audit committee proxied by the size of audit committee and meeting of audit committee had no effect of intellectual capital disclosure. In the other side, financial ratio was proxied by profitability had positive significant effect of intellectual capital disclosure, while leverage had negative effect of intellectual capital disclosure.